2010
DOI: 10.1371/journal.pgen.1001002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Functional Genetic Variant at 16q12.1 for Breast Cancer Risk: Results from the Asia Breast Cancer Consortium

Abstract: Genetic factors play an important role in the etiology of breast cancer. We carried out a multi-stage genome-wide association (GWA) study in over 28,000 cases and controls recruited from 12 studies conducted in Asian and European American women to identify genetic susceptibility loci for breast cancer. After analyzing 684,457 SNPs in 2,073 cases and 2,084 controls in Chinese women, we evaluated 53 SNPs for fast-track replication in an independent set of 4,425 cases and 1,915 controls of Chinese origin. Four re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
110
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 18 publications
6
110
0
Order By: Relevance
“…In a consortium including 23,637 breast cancer patients and 25,579 controls of East Asian ancestry, a replication study was conducted of 70 singlenucleotide polymorphisms (SNPs) in 67 independent breast cancer susceptibility loci identified by genome-wide association study (GWAS) primarily in European-ancestry populations (Zheng et al, 2013). In the study (Zheng et al, 2013), only half of the genetic risk variants initially reported in whites were associated with breast cancer risk in the East Asian population; whereas five breast cancer associated SNPs initially identified among Asians Long et al, 2010a;Cai et al, 2011;Long et al, 2012), were replicated in samples of whites which were variants at 6q25, 10q21, 11q24, and 16q12. In other GWAS studies among Asians, new breast cancer risk variants at 6q14, 10q25, and 2q34 were discovered Shi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In a consortium including 23,637 breast cancer patients and 25,579 controls of East Asian ancestry, a replication study was conducted of 70 singlenucleotide polymorphisms (SNPs) in 67 independent breast cancer susceptibility loci identified by genome-wide association study (GWAS) primarily in European-ancestry populations (Zheng et al, 2013). In the study (Zheng et al, 2013), only half of the genetic risk variants initially reported in whites were associated with breast cancer risk in the East Asian population; whereas five breast cancer associated SNPs initially identified among Asians Long et al, 2010a;Cai et al, 2011;Long et al, 2012), were replicated in samples of whites which were variants at 6q25, 10q21, 11q24, and 16q12. In other GWAS studies among Asians, new breast cancer risk variants at 6q14, 10q25, and 2q34 were discovered Shi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…26,27 rs28373882:T4C and rs879162:T4C, are intergenic (chromosomes 4q and 16p, respectively) and rs12606061:C4T is located in an intron of CCDC178, a gene of unknown function. The SNP in TOX3 (rs4784227:C4T) that was ranked fourth in the main analysis and second in the analysis that excluded the known BRCA-positive families, is a known susceptibility locus first identified in a breast cancer GWAS by Long et al 28 It has since been replicated in investigations among women of many ethnicities. [29][30][31][32][33] Presence of the variant allele (T) increases the chromatin's affinity for FOXA1, 34 a pioneer factor that can bind to chromatin and recruit the ER, thereby facilitating estrogen-driven transcription and cellular changes.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 56 publications were identified, and full versions of 4 publications were retrieved, from which we selected 20 genome-wide significant SNPs from four publications (18)(19)(20)(21) for genotyping. Four SNPs identified as breast cancer susceptibility loci in a then unpublished GWAS from the Asian Breast Cancer Consortium were also included for genotyping (22).…”
Section: Selection Of Snpsmentioning
confidence: 99%